PENGARUH KUALITAS AUDIT INTERNAL TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL SATUAN KERJA PERANGKAT DAERAH DI LINGKUNGAN PEMERINTAH KABUPATEN LUMAJANG - Dityatama Dityatama (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2012)
The internal control system (ICS) in the local government of Lumajang regency was not effective. We guess that the problem because of the internal audit quality (IAQ) that held was poor. The purpose of this research was to assess the influence of internal audit quality (IAQ) to the auditee's internal control system (ICS) effectivity.Based on a questionnaire survey of an 22 Inspektorat's auditor teams of Lumajang regency, data are analysed using a Component Based Structural Equation Model (CBSEM) with Smart-PLS program. The result showed that : there was asignificant positive influence of internal audit quality (IAQ) to the effectiveness of auditee's internal control system (ICS). These results suggest that to improve the effectiveness of auditee's ICS, can conduct through improve the IAQ withincreasing the skills and personal qualities of internal auditor, the effectiveness of the audit process, and the reliability and usefulness of internal audit reporting.